Aerobic rice Growing Rice Successfully in Water-Shortage Areas of Eastern India - Kumar, Santosh; Dwivedi, S. K.; Singh, S. S.; Sundaram, P. K. (Indian Farming, 2016)
The challenge of increasing water scarcity and frequent occurrence of drought has been identified as the key to low rice productivity in irrigated and rainfed lowland ecosystems of eastern region, threatening food security. Aerobic rice is a new concept of growing rice that requires less water. Compared with lowland rice, water inputs in aerobic rice are more than 40-50 percent lower, water productivity 40-75 % higher and labor use 30-40 % lower and could be a viable alternative for water-short areas in the country. Adoption of high-yielding, good-quality, inputresponsive and drought tolerant aerobic rice varieties will play proactive and decisive role in developing sustainable food production and lead to food security among farm families in the water scarcity prone irrigated and rainfed lowland areas of eastern region of India.